Theoretical Calculation of Photon Emission from Quark-Antiquark Annihilation Using QCD Theory - elaf Mohammed Ahmed; Hadi J. M. Al-Agealy; Nada Farhan Kadhim (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2022)
In this work, we calculate and analyze the photon emission from quark and anti-quark interaction during annihilation process using simple model depending on phenomenology of quantum chromodynamic theory (QCD). The parameters, which include the running strength coupling, temperature of the system and the critical temperature, carry information regarding photon emission and have a significant impact on the photons yield. The emission of photon from strange interaction with anti-strange is large sensitive to decreases or increases there running strength coupling. The photons emission increases with decreases running strength coupling and vice versa. We introduce the influence of critical temperature on the  photon emission  rate in order to facilitate its further applied in  photon emission spectrum. Photon emission was increased with large critical temperature MeV comparing with photons emission at critical temperature MeV. We analyze and discuss the sensitive of the emission of photon to photons energy . It increases with decreased photons energy and vice versa. However, the photons emission increases with increases thermal energy of system T = 170 MeV to 270 Mev. It is implied that strength coupling, critical temperature and photons energy  can be as important as thermal energy of  system   for emission of  photon.